NEW SIRENIAN FINDINGS FROM CRETE ISLAND - Svana, K.; Iliopoulos, G.; Fassoulas, C. (Bulletin of the Geological Society of Greece, 2010)
In the last five years, the discovery of several new localities of fossil Sirenians found in the Neogene sediments of Crete has increased drastically the number of sirenian localities on the island. Some of the most important findings consist of almost complete post cranial skeletons (localities of Stilos, Panassos near Zaros and Tripitos in Agia Fotia near Siteia). Furthermore, the locality Kotsiana near Chania, where in 1973 Symeonidis and Schultz reported the first sirenian findings from Crete, was revisited and several new sites were recorded. The most recent findings not thoroughly studied yet, are situated in three new fossiliferous sites near Panassos village (Ampelouzos, Panasos 2 and Kefala), and in Afrata at Rodopou peninsula. The preliminary morphological and metrical study of the remains from Panassos and Tripitos, and their comparison with other findings from Crete, as well as with Sirenian material from European localities, has shown that all studied individuals belong to the species Metaxytherium cf. medium (Desmarest 1822). The age of the studied Cretan Sirenian material has been determined as Late Miocene (Tortonian) and the presence of Sirenia in Crete indicates the prevalence of shallow and warm marine environments in coastal areas, rich in sea weeds.